1998
DOI: 10.1046/j.1365-2605.1998.00081.x
|View full text |Cite
|
Sign up to set email alerts
|

The epidemiology of erectile dysfunction and its risk factors

Abstract: Erectile dysfunction (ED) affects millions of men throughout the world. The literature is ample, but an accurate estimate of its prevalence is still difficult since figures mainly refer to the USA, and are based mostly on small selected samples of people. Caution must anyway be used in comparing data from studies conducted in the past because of possible differences in the definition and classification of ED. Many factors are believed to contribute to the development and maintenance of ED. The influence of age… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
117
0
11

Year Published

2000
2000
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 161 publications
(129 citation statements)
references
References 35 publications
1
117
0
11
Order By: Relevance
“…The present study was conducted among patient with vascular disorders, which predispose patients to development of ED (4, 20). The study results showed significant increase in HRR in patients subjected to cardiac rehabilitation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The present study was conducted among patient with vascular disorders, which predispose patients to development of ED (4, 20). The study results showed significant increase in HRR in patients subjected to cardiac rehabilitation.…”
Section: Discussionmentioning
confidence: 99%
“…Cardiac rehabilitation improved the IIEF-5 score; however, the change in EQ due to training was negatively related to age and initial EQ. In the literature, the risk of sexual disorders among men with IHD is 39%–65% (7, 20). Furthermore, autonomic dysfunction is among the known etiologic factors of ED (7).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Further, the degree of ED is related to the number and severity of the risk factors themselves. 1,19,20 Recent studies have shown that the similar pathogenic involvement of the nitric oxide (NO) pathway leading to the early impairment of endothelium-dependent vasodilatation and late obstructive vascular changes is common to both ED and other vascular diseases. 21,22 In 2003, a pathophysiological mechanism, the 'artery-size hypothesis,' was proposed by Montorsi et al to explain the link among ED, CAD, and stroke.…”
Section: Discussionmentioning
confidence: 99%
“…17 Questions 1-5 and 15 of the IIEF constitute the erectile function domain, which is used to assess global erectile function. Scoring the IIEF domain of erectile function allowed the classification of each patient as follows: absent of ED (26)(27)(28)(29)(30), mild ED (17)(18)(19)(20)(21)(22)(23)(24)(25), moderate ED (11)(12)(13)(14)(15)(16) and severe ED (0-10).…”
Section: Methodsmentioning
confidence: 99%